?m-Weighted Statistical Convergence - Et, Mikail; Kandemir, Hacer Sengul; Cakalli, Huseyin (Amer Inst Physics, 2021)
In this study, we introduce and examine the concepts of Delta(m) weighted statistical convergence and Delta(m)-weighted (N, p(n)) summability. Also some relations between Delta(m)-weighted statistical convergence and Delta(m) weighted (N, p(n))-summability are given.
4th International Conference of Mathematical Sciences (ICMS) -- JUN 17-21, 2020 -- Maltepe Univ, ELECTR NETWORK
Keywords: Weighted statistical convergence; difference sequence; Cesaro summability; density